Efficacy of lower arch leveling, lower incisors’ root resorption, and pain associated with the correction of curve of Spee using different orthodontic archwires: a randomized clinical trial - Yousef H. Nasrawi (14146809) (2022)
Objectives To compare between 3 archwires (AWs) for leveling curve of Spee (COS) in terms of efficacy of reduction, external apical root resorption (EARR), pain experienced, and the lower arch dimensional changes during COS leveling. Trial design Randomized clinical trial. Setting Jordan University of Science and Technology Postgraduate dental clinics. Material and methods Fifty-three subjects with COS > 5 mm were included in this study. The subjects were randomly divided into three groups based on the AW used: group 1, 0.017 × 0.025-inch stainless-steel (SS) AW; group 2, 0.019 × 0.025-inch SS AW; and group 3, 0.021 × 0.025-inch β-titanium (TMA) AW. The intervention was randomly allocated using the permuted random block size of 3 with a 1:1:1 allocation ratio. In the three groups, a 5-mm depth reverse COS was placed in the AWs. The following time points were defined for COS assessment: T1, before interventional leveling AW placement; and T2–T7, 1–6 months after interventional leveling AW placement. Records consisted of dental study models and periapical (PA) radiographs. Pain scores were recorded using visual analogue scale. Patients were followed up on a monthly basis until COS < 1.5 mm. Main outcome measures COS depth reduction, lower incisors’ EARR, pain scores, and arch dimensional changes. Results An overall reduction of 3.82 mm, 4.47 mm, and 3.85 mm of the depth of COS was achieved in groups 1, 2, and 3, respectively. The mean differences of 0.65 mm between groups 1 and 2 and 0.62 mm between groups 2 and 3 were significant at P < 0.05. Lower incisors’ EARR during leveling COS ranged from 0.68 to 0.72 mm, from 0.63 to 0.82 mm, and from 0.53 to 0.88 mm in groups 1, 2, and 3, respectively (P > 0.05). Higher pain scores were reported by group 2 subjects during the first 24 h. Arch length and width increased significantly in groups 2 and 3 (P < 0.05). In all groups, COS leveling was achieved by lower incisor intrusion and proclination and lower molar extrusion. Conclusions All investigated AWs were effective in leveling COS with minimal lower incisors’ EARR (< 1 mm). COS was leveled by lower incisors’ intrusion and proclination and lower molar extrusion. Pain scores were the highest in group 2 during the first 24 h. Clinical relevance The 3 investigated leveling AWs were effective for the leveling COS and at the same time safe on the roots of the lower anterior teeth. Other Information Published in: Clinical Oral Investigations License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00784-022-04672-x